2022
DOI: 10.1002/pbc.29882
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid hemangioendothelioma in children: The European Pediatric Soft Tissue Sarcoma Study Group experience

Abstract: The European pediatric Soft tissue sarcoma Study Group analyzed all children with epithelioid hemangioendothelioma prospectively registered in the NRSTS-05 (EUDRACT 2005-001139-31) and in MTS-2008 (NCT00379457) studies: 10 patients with localized and one with metastatic disease. Median age was 14.3 years (range, 9.0-18.8). Local therapy was initial primary surgery in seven cases, and five patients received systemic therapy. No patients received radiotherapy. After a median followup of 50 months (range, 6-176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Non-soft tissue epithelioid hemangioendothelioma can also be seen in different organs. Although the liver is the most commonly affected organ, the tumor can develop anywhere with visceral or soft tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-soft tissue epithelioid hemangioendothelioma can also be seen in different organs. Although the liver is the most commonly affected organ, the tumor can develop anywhere with visceral or soft tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no established therapeutic algorithm. Although chemotherapy has been administered in some patients, it has been reported that the most durable solution is complete surgical removal of the tumor tissue [ 3 - 5 ]. This article reports the case of a 15-year-old girl with massive hemangioendothelioma at the cervicothoracic junction.…”
Section: Introductionmentioning
confidence: 99%
“…It originates from precursor cells with endothelial properties and specific fusion genes [ 2 , 3 , 4 , 5 ]. EHE has a peak incidence in middle age; however, the range is broad, with children also being affected [ 1 , 6 , 7 ]. The tumor can occur in any part of the body but commonly affects the lungs, liver and soft tissue and more rarely bone [ 1 , 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%